MENTAL HEALTH OF THE ELDERLY POPULATION AMID PANDEMIC COVID-19 - Caldas, Luiza Thayline Vieira; Alcântara, João Victor da Silva; Arraes, Paula Pably Batista; Dias, Priscila Teixeira; Oliveira, Ramille Gonçalves; Rolim Neto, Modesto Leite; Nobre, Camila Bezerra (Amadeus International Multidisciplinary Journal, 2020)
Abstract: With the reality of the pandemic by COVID-19 extending to alarming levels, the coexistence forced by the need for social withdrawal, We observe the difficulty of maintaining mental stability increasingly discussed. The fear of contracting the disease, as well as thinking about its consequences, makes the population anxious. In this sense, age presents itself as the major risk factor for more severe manifestations of the disease, hence, elderly people are at greater vulnerability for the development of psychological and psychiatric disorders. It is important to ask how our elderly people are living, if a pandemic scenario would really be necessary for the population in question to have visibility. Talking about the health of the elderly both mentally and physically is everyone's duty. In any circumstance, it is up to society to ensure that they can live with health, vitality and the quality of life that every human being deserves. Keywords: COVID-19; Pandemic; Old people; Mental health.